2014
DOI: 10.1002/2013jd021442
|View full text |Cite
|
Sign up to set email alerts
|

Low‐altitude summer/winter microphysics, dynamics, and CCN spectra of northeastern Caribbean small cumuli, and comparisons with stratus

Abstract: Low-altitude cloud microphysics and cloud condensation nuclei (CCN) spectra are presented and analyzed from two cumulus cloud aircraft field campaigns, Ice in Clouds Experiment-Tropical (ICE-T) and Rain in Cumulus over the Ocean (RICO), in the same eastern Caribbean location at opposite seasons. These are further compared with two previously analyzed stratus cloud aircraft campaigns off the central California coast, Physics of Stratocumulus Tops (POST) and Marine Stratus/Stratocumulus Experiment (MASE). Multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 52 publications
(69 reference statements)
0
18
0
Order By: Relevance
“…The influences on cloud and drizzle microphysics noted here are similar to the effects of higher CCN concentrations, N CCN , that is, mainly anthropogenic CCN that cause IAE (e.g., Hudson & Li, 1995;Hudson & Svensson, 1995;Hudson & Yum, 2001;Yum & Hudson, 2001b;Yum & Hudson, 2002Hudson & Mishra, 2007;HN14a;Hudson & Noble, 2014b). The difference is that the results presented here consider CCN spectral shape not N CCN at any specific S. This accounts for the variability of S eff caused by N CCN and σ w variations.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The influences on cloud and drizzle microphysics noted here are similar to the effects of higher CCN concentrations, N CCN , that is, mainly anthropogenic CCN that cause IAE (e.g., Hudson & Li, 1995;Hudson & Svensson, 1995;Hudson & Yum, 2001;Yum & Hudson, 2001b;Yum & Hudson, 2002Hudson & Mishra, 2007;HN14a;Hudson & Noble, 2014b). The difference is that the results presented here consider CCN spectral shape not N CCN at any specific S. This accounts for the variability of S eff caused by N CCN and σ w variations.…”
Section: Discussionmentioning
confidence: 85%
“…This is especially demonstrable for cases without an LWC c cloud threshold. Further along this line, Hudson and Noble () showed that cloud subadiabaticity minimally disrupted ICE‐T N CCN ‐ N c relationships in cumulus clouds where entrainment generally has a greater impact on cloud microphysics than is the case for stratus clouds such as MASE. H15 noted that the variability of N CCN and N c among the MASE flights could not be tied to the minimal air mass trajectory variability that was observed.…”
Section: Discussionmentioning
confidence: 97%
“…Here we present high‐resolution CCN spectra from two of the most recent projects. MASE was done in polluted stratus clouds off the central California coast in July 2005 [ Hudson , ; Wang et al ., ; Hudson and Noble , , hereafter HN14a; Hudson and Noble , , hereafter HN14b]. The CCN and cloud microphysics measurements during MASE are described in HN14a.…”
Section: Measurementsmentioning
confidence: 99%
“…Therefore, another difficulty encountered in aerosol research is the relationship between aerosol particles and cloud droplets. Researches including observations near the ground and many extensive aircraft measurements have focused on the activation properties of aerosols and CCN (Junge and McLaren, 1971;Fitzgerald, 1973;Hudson and Yum, 2001;Hudson, 2002, 2004;Frank et al, 2006;Dusek et al, 2006;Hudson and Mishra, 2007;Kuwata et al, 2008;Hudson et al, , 2010Hudson et al, , 2012, 2014a, 2014bDeng et al, 2011Deng et al, , 2013.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%